(untitled) (Research, Society and Development, 2022)
Chikungunya fever is a viral disease caused by the CHIK virus, this pathology spreads through the vector belonging to the genus Aedes spp. This virus belongs to the group of arboviruses, commonly found in places in tropical climates, it was isolated in Tanzania in 1952. However, it has symptoms similar to other arboviruses causing confusion, making it difficult to identify, the symptoms frequently observed in patients with this viremia are headache, arthralgia, myalgia, tenosynovitis, in some cases it evolves to a chronic form of the disease causing persistent damage to the joints. The objective of this work was to understand the functioning of the laboratory diagnosis of chikungunya fever associated with rheumatological damage. This study is a literature review developed using research published in several databases, SciELO and MEDLINE, using the descriptors chikungunya, CHIK, arbovirus, laboratory diagnosis, chikungunya fever. In this study, we were able to show the importance of laboratory diagnosis in the identification of chikungunya and its association with rheumatologic diseases. Finally, we conclude that the laboratory diagnosis contributes to the identification of the disease in an early and effective way and provides an efficient treatment, and through this it helps in the awareness of the population of the precautions to be taken to avoid infection.